(untitled) (Educational Dimension, 2023)
In this article the history of Germans, including German and Austrian prisoners of war, on the territory of modern Southern Ukraine was researched. Completely new facts were discovered, which make a significant contribution to the development of historical research. All sorts of things related to the history of one’s own hometown were touched upon, as far as the subject is concerned. But on the other hand, these newly discovered materials can be used as teaching material, which realizes the idea of integration of science and education. All the collected material was realized in a series of exercises aimed at the formation and development of various linguistic skills in reading, listening, writing and speaking. This idea has already been practically implemented in the teaching activity: Within the framework of the conducted teaching and research project, places were identified where the German prisoners of war were housed and worked in the Dnipropetrovsk region; buildings built by German prisoners of war according to the projects developed by German engineers; the German traces in different spheres of life in our region and our hometown were researched.